Analysis of Quality of Life of Children With Tuberculosis (8-14 Years) in Banyumas Regency 2023 - Rahayu, Febianti; Nurlaela, Sri; Rejeki, Dwi Sarwani Sri (Insights in Public Health Journal, 2024)
Tuberculosis (TB) of school-age children (5-14 years) increases significantly every year in Banyumas Regency. Children with TB infection can be a source of TB disease can reduce the quality of human resources and quality of life in the future. It takes information on the quality of life of children TB systematically and more in-depth. This study aims to determine the quality of life of children with TB based on 7 aspects and characteristics with descriptive quantitative method of case study design. The population of all TB patients aged 8-14 years has treatment status in Banyumas Regency in 2022-March 2023. Research samples were 72 with Total sampling method. Data collection with questionnaire interviews and TACQOL CF instruments that have been translated and tested for reliability validity and univariate data analysis. Characteristics of TB patients aged 8-14 years in Banyumas Regency, the average age is 10 years old, male (68.1%), and educated in elementary school (80.6%). Most are in Sumbang District (15.3%), confirmed in February 2023 (25%). Clinical characteristics were BCG immunization (97.2%), normal nutritional status (56.3%), type of pulmonary TB (93.1%), advanced stage (75%), type of scoring diagnosis (83.3%), no OAT side effects (73.6%), no comorbidities (66.7%), and family history of TB (52.8%). The quality of life of the study subjects was moderate (51.4%), with the most aspects of the good category on positive emotions (25%) and the less good category on motor function (23.6%) and daily habits (23.6%). The total quality of life of the study subjects was good at best on the aspects of positive emotions and poor quality of life only on the aspects of daily habits. Any difficulties and disorders symptoms are experienced most when the condition is sick and mild pain. Keywords: Characteristics, Quality of Life, Childhood Tuberculosis